EPLERENONE VS IRBESARTAN AS FIRST LINE THERAPY IN OBESE HYPERTENSIVE PATIENTS: PRELIMINARY RESULTS FROM HEBRO STUDY. (June 2022) - Kouremeti, Maria; Iliakis, Panagiotis; Konstantinidis, Dimitrios; Polyzos, Dimitrios; Andrikou, Ioannis; Drogkaris, Sotirios; Tatakis, Fotis; Manta, Eleni; Leontsinis, Ioannis; Zamanis, Ioannis; Siafi, Eirini; Dimitriad, Kyriakos; et al.
Abstract : Objective: Obesity is significantly associated with adverse cardiovascular outcomes. The relationship between obesity and hypertension is well described with obese patients having two times the incidence of developing increased blood pressure (BP). However, little is known about the impact of aldosterone blockade using eplerenone on hypertensive obese patients as first line therapy. The aim of this study was to compare the efficacy between eplerenone and irbesartan in obese hypertensive subjects. Design and method: A prospective, randomized, open-labeled, multicenter trial enrolled 54 hypertensive patients aged 30 to 75 years old, with obesity [body mass index BMI > or = 30 kg/m2)], evaluated by home BP, office BP and ambulatory BP measurements. Subjects randomly received 25 mg eplerenone twice daily or 150 mg irbesartan every morning. The primary endpoint were systolic and diastolic BP after 2 months of follow up. Results: In 54 hypertensive obese patients [53.7% women, mean age 55.8 ± 10.9 years, BMI 34.6 ± 3.1 kg/m2, mean office BP 146.4 ± 9.7/91.8 ± 9.8 mmHg and mean ABP 140.9 ± 7.9/84.6 ± 8.2 mmHg] there was no significant difference in the reduction of systolic ABP between irbesartan and eplerenone (11 ± 14.8 vs. 7 ± 14.7, p = 0.11), nor in the reduction of diastolic ABP (5 ± 8.3 vs. 3.8 ± 9.7, p = 0.13). Moreover, there was no difference in the reduction of OBP in irbesartan group (12 ± 11.3 vs. 9.4 ± 12.7, p = 0.14) in comparison with eplerenone group (7.1 ± 8.7 vs. 2.8 ± 8.7, p = 0.11). Also, there was no statistical significant change in renal function parameters and electrolytes levels in both groups Conclusions: this study suggests that eplerenone does not differ in efficacy and safety compared to irbesartan, an established angiotensin receptor antagonist, as first line therapy in obese hypertensive patients.